`@` `\text {Ans}`
`\downarrow`
`a)`
`(2x - 1)^2 + 1 = 26`
`\Rightarrow (2x - 1)^2 = 26 - 1`
`\Rightarrow (2x - 1)^2 = 25`
`\Rightarrow (2x - 1)^2 = (+-5)^2`
`\Rightarrow`\(\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\)
`\Rightarrow`\(\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\)
`\Rightarrow`\(\left[{}\begin{matrix}x=6\div2\\x=-4\div2\end{matrix}\right.\)
`\Rightarrow`\(\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
Vậy, `x \in`\(\left\{-2;3\right\}\)
`b)`
`(2x - 4)^3 + 2 = 66`
`\Rightarrow (2x - 4)^3 = 66 - 2`
`\Rightarrow (2x - 4)^3 = 64`
`\Rightarrow (2x - 4)^3 = 4^3`
`\Rightarrow 2x - 4 = 4`
`\Rightarrow 2x = 8`
`\Rightarrow x = 8 \div 2`
`\Rightarrow x = 3`
Vậy, `x = 3`
`c)`
\(7^{x+2}+5\cdot7^{x+1}+15=603\)
`\Rightarrow 7^x . 7^2 + 5 . 7^x . 7 = 603 - 15`
`\Rightarrow 7^x . 7^2 + 35 . 7^x = 588`
`\Rightarrow 7^x . (7^2 + 35) = 588`
`\Rightarrow 7^x . 84 = 588`
`\Rightarrow 7^x = 588 \div 84`
`\Rightarrow 7^x = 7`
`\Rightarrow 7^x = 7^1`
`\Rightarrow x = 1`
Vậy, `x = 1.`
\(#48Cd\)